Analisis Permodelan Laju Kehilangan Tanah Akibat Variasi Hujan Menggunakan Rainfall Simulator (Uji Eksperimental Laboratorium) - Dewi, Tiara Servita; Romdania, Yuda; Herison, Ahmad; Ashruri, Ashruri (Jurnal Teknik Sipil, 2025)
Soil erosion affects the quality level of soil carrying capacity. This happened in the TP PKK Collective Garden in Bandar Lampung City, which experienced fertility degradation due to reduced soil nutrient content. The purpose of this study is to analyze the effect of slope variations with variations in rainfall intensity on the magnitude of erosion in non-vegetated soils and to identify control strategies that can be applied. The method used in this study is to use a Rainfall Simulator with variations in the slope and intensity of rain on non-vegetation soils. The results of the calculation of the highest erosion rate of 14.91 tons/ha occurred at (slope of 45% with a rain intensity of 1.75 liters/minute), while the lowest erosion rate of 1.67 tons/ha occurred at (slope of 8% with a rain intensity of 0.75 liters/minute). Statistical analysis showed that the relationship between erosion rate and rainfall intensity and slope had a determination coefficient close to 1, indicating that these variables had a significant influence on erosion rate. The conclusion is that the rate of erosion increases along with the slope and the intensity of rainfall, therefore efforts to reduce erosion by planting plants, planting plant residues, making terraces, and using chemical or natural prepats.